Dimensions of Islamic Theology: Analysis of Theological Verses Based on Asbab al-Nuzul - Damanik, Agusman; Mahendra, Andi; Lubis, Alim Muhadi; Nasution, Anwar Hidayat (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research aims to determine the dimensions of Islamic theology based on the verses of the Koran which are analyzed based on Asbab al-Nuzul. Islamic theology not only includes an understanding of Allah and His teachings, but also includes an understanding of the relationship between humans and their creators, as well as the daily life implications of these teachings. This research uses descriptive qualitative research methods. Thus, the results of this research show that first, the concept of monotheism of Allah as contained in the QS. al-‘Alaq verses 1-5, highlights the greatness and oneness of Allah as the creator of the universe and the source of all knowledge. These verses emphasize the importance of science and education in the Islamic religion, as well as strengthening the theological foundation of Islam about the oneness of Allah and the importance of learning. Second, the concept of the afterlife or doomsday, taking into account Asbab al-Nuzul, especially in the QS. al-Qiyamah verses 6-9, emphasizes the truth and certainty of resurrection and the Day of Judgment, as well as the importance of preparation and responsibility in the afterlife for every individual. These verses confirm Muslims' belief in the Day of Judgment as an integral part of their beliefs. Third, the concept of freedom in Islam, which is analyzed through Asbab al-Nuzul QS. Yusuf verse 99, emphasizes the importance of freedom to choose forgiveness and forgiveness, freedom from hostility and revenge, and freedom in achieving spiritual salvation. This verse provides an example of the importance of choosing the path of peace and forgiveness in human relationships. Thus, the text provides an in-depth understanding of Islamic theological concepts, including the concepts of Allah, the afterlife, and freedom, and shows how these concepts are reflected in the verses of the Qur'an by considering Asbab al-Nuzul.